Effect of Family-Centered Maternity Care (FCMC) on Postnatal Depression Among Mothers: A Quasi-Experimental Study - Oktavia, Sesmi Nanda; Kanathasan, Jayasree S. (Journal of Health Science and Medical Therapy, 2025)
Postnatal depression remains a critical public health concern that adversely affects both maternal well-being and infant development, particularly in low-resource settings. This quasi-experimental study aimed to examine the effect of Family-Centered Maternity Care (FCMC) on the incidence and severity of postnatal depression among postpartum mothers in the working area of Puskesmas Lubuk Alung, Indonesia. A total of 85 postpartum mothers were recruited, and 30 received a structured two-week FCMC intervention involving home visits, emotional support, and health education delivered with family involvement. Postnatal depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS) before and six weeks after the intervention. The results revealed a significant reduction in the prevalence of depressive symptoms, decreasing from 73.3% to 20.0% (p = 0.0001). Multivariate analysis showed that low family support (AOR = 13.28), low maternal education (AOR = 5.45), and emotional stress within the first 72 hours postpartum (AOR = 8.76) were significant predictors of postnatal depression. Although age and parity were not statistically significant, younger and primiparous mothers showed higher tendencies toward depressive symptoms. These findings underscore the importance of integrating FCMC into postpartum care services, particularly in culturally collectivist societies where family involvement can enhance maternal psychological resilience. Early implementation of FCMC may offer a cost-effective and scalable strategy to address postnatal mental health challenges and improve overall maternal health outcomes in primary care settings.